Manage your time better - Heitz, Bill; Brown, Rick (Chicago : Jack Wilson and Associates)
This training program shows how to virtually'add' minutes to each day by forming a logical, prioritized sequence or'plan of action' that incorporates the use of symbols, notes, teamwork, clear communication processes and much more
Writer, Dr. Paul, R. Timm, Rick Brown
Keywords: Time management